Sistem Distribusi Pengiriman Sparepart Motor Honda dengan Pendekatan Saving Matrix dan Metode Nearest Neighbor - Nalhadi, Ahmad; Wiliyanto, Reza; Supriyadi, Supriyadi; Hayyin, Fajar (Fakultas Teknik Universitas Tulang Bawang, 2025)
This research focuses on distribution management issues in Indonesia, with an emphasis on high logistics costs (23.5% of the national Gross Domestic Product in 2021). PT. XYZ, as the main dealer for Honda motorcycles, faces distribution strategy challenges due to various factors such as an extensive distribution network, fluctuations in delivery demand, variations in delivery vehicle capacity, and high delivery costs. The research objective is to develop a distribution strategy for Honda motorcycle spare parts to obtain optimal delivery routes. The approach used is the Saving Matrix and Nearest Neighbor method, based on actual demand data for Honda motorcycle spare parts from January 3rd to January 14th, 2023, involving 81 distribution network points. The research results indicate that the new route yields a distance savings of 1006.92 kilometers with a distance efficiency of 28.61% and a fuel cost savings of Rp. 2,152,771,- with a fuel cost efficiency of 26.64% compared to the initial route. The creation of a web-based route formation application interface aims to be dynamic and can be used anytime to facilitate daily route formation for deliveries. Keywords: Distribution Strategy, Interface Design, Logistics, Nearest Neighbor, Saving Matrix